Factors associated with consumption of fruits and vegetables in medicine students of a peruvian university - Huamancayo-Espíritu, Alan (2019)
Aim: To determine the prevalence and factors associated with the low consumption of fruits and vegetables in students of the professional career of human medicine of the Universidad Nacional Hermilio Valdizán (UNHEVAL). Material and methods: Cross-sectional study. The population was constituted by 371 students of the professional career of Human Medicine who were enrolled and taking courses in July 2018. It was applied a self-administered questionnaire which allowed to obtain information about the consumption of fruits and vegetables. From the collected data it was obtained the prevalence and factors associated with low consumption of fruits and vegetables. Results: The prevalence of low consumption of fruits and vegetables was 60.1% (IC95%: 55.0% -65.2%). The main reasons for not consuming fruits and vegetables were that it is rare to get them in the cafeterias of the university (78.71%), insufficient time for their selection, purchase and preparation (73.58%) and living with one of the parents who were in charge for their feeding. (55.26%). The multivariate analysis found that the only factor associated with low consumption of fruits and vegetables was the insufficient time for selection, purchase and preparation; whereas, living with one of the parents constituted a factor protector. Conclusion: There is a high prevalence of low consumption of fruits and vegetables in students of the professional career of human medicine of the UNHEVAL. The insufficient time for the selection, purchase and preparation of fruits and vegetables is an associated factor and living with one of the parents constitutes a protector factor.